Optimizing SMEs Through Digital Design for Sustainable Industrial Development - Limano, Ferric (Bina Nusantara University, 2024)
SMEs (Small and Medium Enterprises) are the pillars of Indonesia's economy, as evidenced by their significant contribution to the country's gross domestic product. The digital disruption era, particularly during the pandemic, has necessitated changes in product development and marketing strategies for SMEs, pushing them towards digital approaches. This research aims to study the application of digital design in branding and digital marketing strategies by SMEs, providing recommendations based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The qualitative research method utilized data from two product samples: Maicih (Food) and Compass (Fashion). In the case of Maicih, engagement was built through a viral snack brand known for its unique spicy flavors, enjoyed socially. The brand's social media, featuring the tagline